SPECIAL NEEDS CHILDREN IN SCHOOL (INCLUSION): QUANTITATIVE STUDY ON STUDENT ATTITUDES - Makris, Ioannis; Macri, Dimitra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The study’s goal is to pinpoint student attitudes relating to the presence of special needs students in ordinary schools. The study was based on Triandis’ conceptual model regarding attitudes (Triandis, 1971). The Chedoke-McMaster Stroke Assessment (CMSA) was the tool we chose and, in particular, the Chedoke-McMaster Attitudes towards Children with Handicaps (CATCH) scale to measure the attitude of ordinary students towards handicapped students. Our sample includes data from schools in the seven countries (France, Greece, Italy, Romania, Belgium, Portugal, and Poland) participating in the Erasmus+ “Heading for inclusive school in Europe” program, with APAJH/LOT, France, as the leader. Our study implemented descriptive and deductive statistical analyses and our ANOVA model pointed to the statistically important factors. Based on those findings, interesting associations were revealed which helped us fathom young people’s views on handicaps; and redefine the issue of inclusion of handicapped students in schools. It also allowed us to design a broader dynamic regarding the agencies championing this inclusion effort. Last, our conclusion has been that, in order to redefine the issue of special needs students, all involved should modify their own attitudes and perceptions.